Questionnaire‐based Analysis of Owner‐reported Scratching and Pain Signs in Cavalier King Charles Spaniels Screened for Chiari‐like Malformation and Syringomyelia. (4th November 2017) - Sparks, C.R.; Cerda‐Gonzalez, S.; Griffith, E.H.; Lascelles, B.D.X.; Olby, N.J.
Abstract : Background: Chiari‐like malformation (CM) and syringomyelia (SM) cause a pain syndrome in Cavalier King Charles spaniels (CKCS). Clinical signs are not consistently apparent on neurologic examination, and owner reporting of signs provides vital clinical history. However, owner questionnaires for this disease are not well developed. Objectives: To develop a tool to capture owner‐reported clinical signs for use in clinical trials and to compare owner‐reported signs with the presence of pain on neurologic examination and SM on magnetic resonance imaging (MRI). Animals: Fifty client‐owned CKCS. Methods: Owners completed a questionnaire and pain/scratch map. Each dog underwent a neurologic examination and craniocervical magnetic resonance imaging (MRI). Questionnaire responses were developed into scores, area of shading for pain/scratch maps was measured, and consistency of responses between these tools was assessed. Owner‐reported findings were compared with neurologic examination findings and presence and severity of SM on MRI. Results: Thirty‐three dogs were symptomatic and 17 asymptomatic; 30 had SM. The most common sign of pain was crying out when lifted (n = 11). Extent of shaded areas on maps positively correlated with questionnaire scores for pain ( r 2  = 0.213, P  =   0.006) and scratch ( r 2  = 0.104, P  =   0.089). Owner‐reported findings were not significantly associated with presence or severity of SM or neurologic examination findings. Owner‐reported lateralization of signs was significantly associated with SM lateralization ( P  <   0.0001). Conclusions: The questionnaire and maps may be useful for clinical trials. Lack of association of owner‐reported signs with SM highlights our lack of understanding of the pathophysiology of pain in this disease.